Reflections on the ethics of recruiting foreign-trained human resources for health - Runnels, Vivien; Labonté, Ronald; Packer, Corinne (Université d'Ottawa | University of Ottawa, 2011)
Abstract Background Developed countries' gains in health human resources (HHR) from developing countries with significantly lower ratios of health workers have raised questions about the ethics or fairness of recruitment from such countries. By attracting and/or facilitating migration for foreign-trained HHR, notably those from poorer, less well-resourced nations, recruitment practices and policies may be compromising the ability of developing countries to meet the health care needs of their own populations. Little is known, however, about actual recruitment practices. In this study we focus on Canada (a country with a long reliance on internationally trained HHR) and recruiters working for Canadian health authorities. Methods We conducted interviews with health human resources recruiters employed by Canadian health authorities to describe their recruitment practices and perspectives and to determine whether and how they reflect ethical considerations. Results and discussion We describe the methods that recruiters used to recruit foreign-trained health professionals and the systemic challenges and policies that form the working context for recruiters and recruits. HHR recruiters' reflections on the global flow of health workers from poorer to richer countries mirror much of the content of global-level discourse with regard to HHR recruitment. A predominant market discourse related to shortages of HHR outweighed discussions of human rights and ethical approaches to recruitment policy and action that consider global health impacts. Conclusions We suggest that the concept of corporate social responsibility may provide a useful approach at the local organizational level for developing policies on ethical recruitment. Such local policies and subsequent practices may inform public debate on the health equity implications of the HHR flows from poorer to richer countries inherent in the global health worker labour market, which in turn could influence political choices at all government and health system levels.